Larnite‐Bearing Rock—The Discovery of a New Source of Raw Material in the Production of Neolithic and Chalcolithic Bifacial Tools. (30th September 2014) - Vardi, J.
Abstract : Recently, large‐scale production sites for the production of bifacial tools (axes and adzes) were discovered in the Judean desert. The waste piles have resulted from the numerous knapping procedures carried out at these sites, extend over thousands of square metres and include, in addition to the waste, a profusion of unfinished tools. The raw material procured for their fabrication is larnite‐bearing rock. The larnite‐bearing rock is extremely rare in the Levant. It occurs only in the exposures of the Hatrurim geological formation. The use of larnite for the production of chipped stone tools was entirely unknown until now. This newly discovered production area produced thousands of bifacial tools, the destination of which is as yet unknown.